Representation of Mendoan and Baturaden Indah Songs in Lengger Performances During the Orde Baru Period - Irwanto; Royan Fadli, Akhyar (International Proceedings of Nusantara Raya, 2024)
This study discusses the representation of the Banyumasan Songs in the performance of Lengger during the Orde Baru period. As an art that develops in the Banyumasan community, lengger has become part of the dynamics of the life of its people. Lengger's art during the Orde Baru period was greatly influenced by various interests. The interests in question are often represented through the songs sung during the lengger performance. As a local literature, Tembang Banyumasan is used as a medium to convey various interests. This importance can be seen in several Banyumasan Songs that existed during the Orde Baru period. In this study, the song is titled Mendoan and Baturaden Indah. The analysis used in this paper is a qualitative textual and interpretive study. The lyrics of the Banyumasan Song in the performance of Lengger are interpreted textually, then interpreted by taking into account the situation and conditions during the Orde Baru period. The results of the analysis show that some of the Banyumasan Songs that existed during the Orde Baru period represent the conditions and interests of that time. From the results of the interpretation of the Banyumasan Song above, it is known that the song with the title Mendoan has represented the culinary potential of the Banyumas region. The culinary potential is related to the importance of building an 'image' of the region aimed at providing tourism attraction. Tembang Baturraden Indah, represents one of the natural tourism potentials of the Banyumas area. In addition to describing the natural conditions of the Baturaden Tourist Facility, the song is also a promotional medium for the tourism potential developed during the Orde Baru period.